Bimbingan Teknik Reinforcement dalam Meningkatkan Target Hafalan Santri - Ach. Sofauzzad; Abdul Mughni; Samsul Arifin (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
This article examines reinforcement techniques in memorizing the Al-Quran. Memorizing the AlQuran is a special part that cannot be separated from Islamic boarding school education. Memorizing is not an extracurricular lesson like in public schools. However, it is one of the main lessons at Islamic boarding schools. In Islamic teachings, memorizing the Al-Quran is a command from Allah SWT. The type of research used is descriptive qualitative. This research observes the implementation of guidance using reinforcement techniques carried out by teachers at the Ma'hadul Qur'an Pondok Pesantren Salafiyah Syafi'iyah Sukorejo to help deal with students' memorization problems. The research results showed that the guidance process using reinforcement techniques was successful. Guidance is carried out using behavioral therapy, then continued with reinforcement techniques. The results of this technique can make students aware that what they have been doing so far can be detrimental to themselves and these students realize that successful people are diligent people, not lazy people.